2023
DOI: 10.3390/molecules28031200
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Natural Pigments’ Extraction, Isolation, and Stability in Food Applications

Abstract: Color in food has multiple effects on consumers, since this parameter is related to the quality of a product, its freshness, and even its nutrient content. Each food has a characteristic color; however, this can be affected by the technological treatments that are applied during its manufacturing process, as well as its storage. Therefore, the development of new food products should take into account consumer preferences, the physical properties of a product, food safety standards, the economy, and application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 160 publications
(133 reference statements)
0
13
0
Order By: Relevance
“…Color is one of the most vital attributes of food considering quality indicators and acceptability [ [1] , [2] , [3] ]. Consumers’ acceptability largely depends on the color, flavor, and taste of products [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Color is one of the most vital attributes of food considering quality indicators and acceptability [ [1] , [2] , [3] ]. Consumers’ acceptability largely depends on the color, flavor, and taste of products [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The common practice for coloring food is to use synthetic azo-dye, which is considered low in cost and high in stability. Recent research revealed that food colored with synthetic dyes is associated with numerous health effects, especially hyperactivity in children [ 3 , 8 , 9 ]. Numerous studies have highlighted the health advantages associated with natural pigments, particularly anthocyanins, and carotenoids [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yellow‐orange bell peppers contain beta‐ and gamma‐carotene, zeaxanthin, lutein, and beta‐cryptoxanthin, while green varieties are rich in chlorophyll and carotenoids (Chouaibi et al, 2019; Marín et al, 2004). These natural pigments not only serve as alternatives to artificial food colorings but also contribute to the pepper's multifunctionality and market value (Echegaray et al, 2023; Gomes et al, 2014; Molina et al, 2023).…”
Section: Introductionmentioning
confidence: 99%